Маркетингові комунікації в системі інноваційного розвитку організацій - Ілляшенко, Сергій Миколайович; Шипуліна, Юлія Сергіївна; Ілляшенко, Наталія Сергіївна (Сумський національний аграрний університет, 2023)
Отримані результати поглиблюють засади інноваційного менеджменту організацій, в частині урахування в системі управління маркетинговими комунікаціями і комерціалізацією інноваційної продукції, особливостей формування і реалізації основних типів стратегій інноваційного розвитку.

The obtained results deepen the foundations of innovation management of organizations, in terms of taking into account in the system of management of marketing communications and commercialization of innovative products, features of formation and implementation of the main types of strategies for innovative development.
Marketing communications in the system of innovative development of organizations
Keywords: інноваційний розвиток; інноваційний менеджмент; маркетинг інновацій; маркетингові комунікації; innovative development; innovation management; marketing of innovations; marketing communications